A selection algorithm for power controller unit of hybrid vehicles - Chin, Hubert H.; Jafari, Ayat A. (2011 14th International IEEE Conference on Intelligent Transportation Systems (ITSC), 2011)
This paper presents an adaptive power management control strategy that is based on selection algorithm for controlling gas engines and electric motor torque. The state of the art hybrid vehicle technology determines the instantaneous power split in order to increase energy efficiency. The selection algorithm, contained by the power controller unit, uses inputs of analog sensors along with commands from driver's desired speed and makes a selection of outputs from preassigned control states. These states are stored in a knowledge base for revealing engine and motor mixed control strategies. The objectives of the control strategies are to minimize fuel consumption, reduce engine-out emissions, maintain higher level safety, and keep passenger and driver's comfort as the current system.